Massive Rotator Cuff Repair With All-Arthroscopic Patch Augmentation: A Surgical Technique. Issue 2 (June 2016) - Levy, David M.; Chalmers, Peter N.; Trenhaile, Scott W.; Bach, Bernard R.; Romeo, Anthony A.; Verma, Nikhil N.
Abstract : Surgical management of massive rotator cuff tears is plagued by structural failure rates as high as 94%. Multiple arthroscopic and open techniques have been described, but there is no current gold standard. Biological healing at the tendon footprint is key to avoiding failure. Xenograft patch placement has been described as a possible technique to augment the biology of rotator cuff repair when tendon quality is compromised. The purpose of this article is to describe an all-arthroscopic technique of patch augmentation for repair of massive rotator cuff tears. Abstract : Supplemental Digital Content is available in the text.